2016
DOI: 10.1093/mnras/stw3017
|View full text |Cite
|
Sign up to set email alerts
|

Multifrequency polarimetry of a complete sample of PACO radio sources

Abstract: We present high sensitivity polarimetric observations (σ P 0.6 mJy) in 6 bands covering the 5.5 − 38 GHz range of a complete sample of 53 compact extragalactic radio sources brighter than 200 mJy at 20 GHz. The observations, carried out with the Australia Telescope Compact Array (ATCA), achieved a 91% detection rate (at 5σ). Within this frequency range the spectra of about 95% of sources are well fitted by double power laws, both in total intensity and in polarisation, but the spectral shapes are generally dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 34 publications
3
43
1
Order By: Relevance
“…At the lowest Planck frequencies and at high Galactic latitudes our present results are in general agreement with other published works on extragalactic radio sources (Sajina et al 2011;Massardi et al 2013;Galluzzi et al 2017). At higher frequencies we are presenting novel results that could be useful in estimating the polarized source number counts and, consequently, the contamination due to these sources for the detection of the primordial CMB E and B mode polarisation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…At the lowest Planck frequencies and at high Galactic latitudes our present results are in general agreement with other published works on extragalactic radio sources (Sajina et al 2011;Massardi et al 2013;Galluzzi et al 2017). At higher frequencies we are presenting novel results that could be useful in estimating the polarized source number counts and, consequently, the contamination due to these sources for the detection of the primordial CMB E and B mode polarisation.…”
Section: Discussionsupporting
confidence: 91%
“…Sajina et al (2011) observed with the Very Large Array, for frequencies from 4.86 to 43.34 GHz, typical values for Π of 2 -5 per cent in a sample of sources selected in the AT20G catalogue with S20GHz > 40 mJy. More recently, Galluzzi et al (2017) found a median value for the polarisation fraction of 2.01 per cent at 33 GHz for their sample of 53 sources selected from the faint PACO sample (Bonavera et al 2011), with S20GHz > 200 mJy. They also found no trend with frequency or flux densities (up to 38 GHz) for Π, in agreement with our current findings.…”
Section: Comparison With Results Based On Detected Extragalactic Compmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysed sample of extragalactic dusty sources (selected from the 857 GHz of the PCCS2 catalogue) shows polarisation properties similar to those characterizing radio sources (Massardi et al 2013;Galluzzi et al 2017;B17). We measure polarization values of Π =(3.10 ± 0.75) per cent and Π = (3.65 ± 0.66) per cent at 217 and 353 GHz respectively, and of Π 2 =(7.38±1.32) per cent and (6.87±1.35) per cent at 217 and 353 GHz, respectively.…”
Section: Discussionmentioning
confidence: 89%
“…The results shown in Table 1 are consistent with previous studies of AGN and DSFGs. Briefly, in previous studies, polarisation fraction is found to be independent of flux (Battye et al 2011;Trombetti et al 2018;Datta et al 2018) and frequency (Battye et al 2011;Galluzzi et al 2017 Weighted Mean 6 − 1500 686 6.9 ± 1.1 2.63 ± 0.22 Table 1. Mean-squared polarisation fractions ( p 2 ) and inferred fractional polarisation ( p 2 ) measurements for Nsource number of SPT-SZ selected sources stacked in flux bins Srange using 95 and 150 GHz SPTpol maps.…”
Section: Comparison To Previous Resultsmentioning
confidence: 89%